Sperm chromatin condensation and single‐ and double‐stranded DNA damage as important parameters to define male factor related recurrent miscarriage. Issue 11 (17th September 2020) - Ribas‐Maynou, Jordi; Abad, Carlos; García‐Segura, Sergio; Oliver‐Bonet, Maria; Prada, Elena; Amengual, Maria José; Navarro, Joaquima; Benet, Jordi
Abstract: The aim of the present work is to characterize the relationship between sperm protamine deficiency and single‐ and double‐stranded DNA damage and to assess the diagnostic potential of chromomycin A3 (CMA3). For that purpose, semen samples from 90 human males with different clinical features were included (fertile donors, patients with recurrent pregnancy loss [RPL], and infertile patients). DNA condensation was analyzed by CMA3 and different types of DNA fragmentation were analyzed through the comet assay. A positive correlation between DNA condensation and single‐stranded DNA fragmentation was found ( R s = .456; p  = .05). CMA3 presented differences between fertile donors and all other groups ( p  < .001). Interestingly, patients with RPL, who were able to achieve a pregnancy, and infertile patients showed similar values of CMA3 ( p  > .05). Receiver operating characteristic curves and the profiles obtained by the combination of Comet assays and CMA3 indicate that the CMA3 test may be an interesting approach to distinguish those subjects with higher pregnancy loss risk from fertile donors (CMA3 area under the curve 0.928, with a confidence interval of 0.849–1.000). The present work shows that DNA condensation is related to oxidative damage, which affects mainly protamine‐rich regions. The profiles observed in different clinical groups showed that CMA3 might be useful for the diagnosis of RPL risk when combined with Comet assays. Abstract : The present work proves the correlation between chromatin condensation and single‐strand breaks and the lack of correlation with double‐strand breaks. Also, receiver operating characteristic curves show that chromomycin A3 may be an interesting approach for the diagnosis of male infertility